Сhronic heart failure impact on stroke index and ejection fraction during polytrauma - Svitlana Lutska (Bogomolets National Medical University, 2022)
Study of the effect of heart failure on the course of hypovolemia during polytrauma with the absence of traumatic myocardial injury. The study involved 95 patients, who were divided into 3 groups. The first Control group (C), 29 patients had no heart failure. The second group was Standard (S), 33 patients suffered from chronic heart failure and received standard therapy according to the protocol. The third group (E) of 33 patients with chronic heart failure who, in addition to standard therapy according to protocol, received Ethylmethihydroxypyridine succinate.  Patients of groups S and E had equal inclusion criteria, namely the main disease leading to chronic heart failure was arterial hypertension, which had existed for more than 5 years. Three groups of patients had no traumatic myocardial injury. The stroke index (SI) during admission of group C is 24.7±4.8 ml/m2, on the 3rd day 32.8±5.0 ml/m2, (p <0.001), and on the 7th day - up to 39.1±6.0 ml/m2, (p <0.001). SI of group S during admission was 22,9±3,7 ml/m2, on the 3rd day 26,9±4,7 ml/m2 (p <0,001), and on the 7th day - 34,6±5,5 ml/m2 (p <0,001). SI of group E patients during admission was 23.4±2.7 ml/m2, on the 3rd day 26.1±1.5 ml/m2 (p < 0.01), and on the 7th - up to 36.8±2.2 ml/m2 (p < 0.01).  Cardiac index (CI) of group C within admission was 2,26±0,35 l/min∙m2, on the 3rd day - 2.73±0.37 l/min∙m2 (p <0,001), and by the end of the study - up to 3.08±0.40 l/min∙m2 (p <0,001). CI of group S during admission amounted to 1,99±0,39 l/min∙m2, on the 3rd day - 2,22±0,31 l/min∙m2 (p <0,02), on 7th - up to 2.67±0.33 l/min∙m2 (p <0.001). CI of group E - 2,0±0,38 l/min∙m2. Until the 3rd day - 2,06±0,30 l/min∙m2 (p> 0.4), at the 7th reached 2.97±0.32 l/min∙m2 (p <0,001). Ejection fraction (EF) of group C within admission amounted to 53.7±3.4%.  In the future, EF has significantly increased, reaching 59.6±5.2% (p <0.001) and 63.3±6.4% by the 7th day (p <0.01). EF of group S during admission was 47,9±4.7%, on the 3rd day it increased to 52.2±5.2% (p <0.001), and on the 7th - to 56.8±6.9% (p <0.001). EF of patients group E within the admission was - 47.5±6.9%. On the 3rd day, the EF authentically increased to 52.3±5.3% (p<0.003), and on the 7th day - to 61.5±6.4% (p <0.001). The inclusion of Ethylmethylhydroxypyridine succinate (EMGPS) in the intensive care scheme of E group patients with chronic heart failure during polytrauma without acute myocardial injury gradually improves myocardial contractility activity (MCA). On the 3rd day after patient's admission, a significant impact of EMGPS on the study of mechanics and energy indicators was not observed. But from the 7th day there was an increase in SI on 6.4% (36.8±1.2 contrary 34.6±5.5 ml/m2, p = 0.03), an increase in EF on 8.3% (61.5± 6.4 contrary 56.8±6.9%, p = 0.005), CI increased on 11.2% (2.94±0.32 contrary 2.67±0.33 l/min∙m2, p < 0.001). Thus, the addition of EMGPS to the intensive care scheme to patients with chronic heart failure during polytrauma without acute myocardium injury optimizes blood circulation and its energy efficiency.  Ethylmethylhydroxypyridine succinate optimizes the energy efficiency of blood circulation in patients with chronic heart failure during polytrauma without acute myocardial injury.